Employee Transfer: a Review of Recent Literature - Budiman, Arif (JPAS (Journal of Public Administration Studies), 2018)
The purpose of this paper is to summarize the current state of research on organization’s support for transferred employee during relocation by identifying and analyzing issues about work relocation. And to present the alternative approaches in handling relocation to be more supportive toward employees. This research used systematic literature review method to conduct a brief selective review of relocation theories and its applications. The results obtained, based on literature reviews and analyses, are the identification of several issues about employee relocation such as stress, relocation packages/programs, willingness to relocate, perceived organizational support (POS), family issue - spouse and children, and politics in transfers. The findings suggest that organizations should be more supportive toward employees.